PENGEMBANGAN KOMPETENSI DAN PENDIDIKAN BERKELANJUTAN PUSTAKAWAN PTAIN: STUDI KASUS DI PERPUSTAKAAN UIN SUNAN KALIJAGA YOGYAKARTA - Masruri, Anis; Kuntoro, Sodiq A.; Arikunto, Suharsimi (Graduate School, Universitas Negeri Yogyakarta, 2016)
Penelitian ini bertujuan mengungkapkan pengembangan kompetensi dan pendidikan berkelanjutan pustakawan UIN Sunan Kalijaga Yogyakarta menurut persepsi pustakawan, pimpinan, dan pengguna perpustakaan. Metode yang digunakan adalah metode kualitatif dengan pendekatan studi kasus di Perpustakaan UIN Sunan Kalijaga Yogyakarta. Hasil penelitian ini adalah sebagai berikut: (1) kompetensi pustakawan UIN Sunan Kalijaga Yogyakarta yang perlu dikembangkan terbagi menjadi enam bidang, yaitu: kompetensi manajerial, kompetensi pengelolaan informasi, kompetensi kependidikan, kompetensi kepribadian, kompetensi sosial, dan kompetensi pengembangan profesi; (2) pendidikan berkelanjutan bagi pustakawan UIN Sunan Kalijaga Yogyakarta dilakukan melalui pendidikan nonformal berbentuk pelatihan dengan mengacu pada prinsip pendidikan orang dewasa (andragogi). Adapun materi yang perlu dipelajari dalam kegiatan pelatihan oleh pustakawan UIN Sunan Kalijaga Yogyakarta meliputi kajian minat dan kebutuhan informasi, seleksi bahan pustaka, pengadaan bahan pustaka, organisasi dan analisis informasi, manajemen perpustakaan, pelayanan informasi, literasi informasi, teknologi informasi, pengembangan kepribadian, dan keterampilan interpersonal.Kata kunci: kompetensi pustakawan, pendidikan berkelanjutan THE DEVELOPMENT OF ADVANCED EDUCATION AND COMPETENCY FOR THE LIBRARIANS OF ISLAMIC STATE UNIVERSITY: A CASE STUDY IN THE LIBRARY OF SUNAN KALIJAGA STATE ISLAMIC UNIVERSITY YOGYAKARTAAbstractThe study was to reveal the development of advanced education and competency for the librarians of Sunan Kalijaga State Islamic University Yogyakarta according to the perception of the librarians, the leaders and the users. The method that the researchers employed was a qualitative method by means of case study approach and the study was conducted in the Library of Sunan Kalijaga State Islamic University. The results of the study were as follows: (1) The competencies for the librarians of Sunan Kalijaga State Islamic Universities that should be developed were divided into six domains namely: managerial competency, information-processing competency, education competency, personality competency, social competency and professional development competency; and (2) The advanced education for the librarians of Sunan Kalijaga State Islamic University should be conducted through a non-formal education in the form of training programs by referring to the principles of andragogy (education for the adult people). However, the materials that should be studied by the librarians of Sunan Kalijaga State Islamic University in the training activities included the interest and information needs analysis, the literary material selection, the literary material procurement, the information organization and analysis, the library management, the information service, the information literacy, the information technology the personality development and the interpersonal skills.Keywords: librarians’ competency, advanced education